INFLAMMATORY REACTIONS IN EXPERIMENTAL MYOCARDIAL DAMAGE - L. D. Khidirova; N. N. Mayanskaya (Рациональная фармакотерапия в кардиологии)
Aim. To study the role of hormonal and metabolic changes specific to myocardial infarction in the development of inflammatory reactions in the experimental non-coronarogenic myocardial damage. Material and methods. Wistar male rats weighing 180–220 g (n=80) were used in the study. Metabolic myocardial infarction in intact rats and rats with alloxan diabetes was induced by epinephrine injected subcutaneously as single dose or daily (7 days). Myocardial infarction was verified by ECG analysis, and by histological control. Nitroblue tetrazolium test (NBT-test) both spontaneous and zymosan induced NBT-test was used to determine the oxygen-dependent functional activity of neutrophils and their biocidal reserve. Determination of cationic proteins in neutrophils of peripheral blood was performed using lysosomal-cationic test. Results. Increase in oxygen-dependent neutrophil biocidal activity was found as well as reduction in biocidal reserves. Indicators of zymosan induced NBT-test raised according to aggravation of hormonal changes much slower: alloxan increased them by 10% only , epinephrine single dose — by 35%, long-term epinephrine administration simultaneously with alloxan — by 54%. At the same time oxygen-independent neutrophil activity determined by intra-neutrophil cationic proteins level was significantly reduced. Blood levels of pro-inflammatory cytokines raised according to progression of the changes in myocardium: tumor necrosis factor-α (from 5.5±0.03 to 12.6±1.23 pg/ml) and interleukin-1β (from 6.0±0.18 to 11.1±0.78 pg/ml). Conclusion. Experimental model of hormonal changes specific to myocardial infarction detected a relationship between inflammatory reactions accompanying myocardial damage and increased catecholamine production.